New perspective of film tourism: a comparative study (2014-2020) - Domínguez-Azcue, Janire; Almeida-García, Fernando; Pérez-Tapia, Gema; Mercade-Mele, Pere (Emerald, 2021)
This study aims to compare film tourism and their activities, before and during the CoViD-19 pandemic. For this purpose, a comparative analysis is carried out between 2014 and 2020, the latter date being affected by the pandemic caused by Covid-19. This study is based on 888 surveys between the mentioned two years, distributed mainly among respondents from Europe and the United States. The results of the research indicate that there are no changes concerning the knowledge of the film tourism term, but differences are observed in the study period regarding the activities linked to this type of tourism, as well as to motivations and travel intentions driven by films or series. Lastly, changes in the popularity or knowledge of film destinations were observed during the study period. The findings of this research are particularly useful for destination managers.
Keywords: Turismo; Marketing; Film tourism; Turismo fílmico inducido; Film-induced tourism; Film destinations; Marketing; COVID-19; Entes de gestión de destinos; DMO